Aktivitas Fisik Animo Wanita Masa Kini dalam Menurunkan Berat Badan - Linda Desrianda Tamher; Mustika Fitri; Pipit Pitriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The study aims to determine the influence of physical activity on obese women. The research design used is Pretest-Posttest Two Treatment Design. The subject that followed the study amounted to 22 obese women, divided into 2 groups, aerobic gymnastics and Zumba groups. The study was conducted 3 times a week, for 12 weeks, with the intemsities of 65 – 85% based on the maximum pulse of each subject. The tool used is Omron Karada Scale. The results of this research on aerobic aerobics and Zumba have been the effect of weight loss. Conclusion of this research of physical activity such as aerobic gymnastics and Zumba is able to lose the weight of obese women. Keyword : Physical Activity, Obese Women, Weight Loss